Mystical words and meanings - reza hoseinifar (حکمت اسرا, 2015)
One`s mind is quickly referred to the meaning from the word by the firm relationship between the word and meaning. The origin and nature of this relation and the form that the Word implies meaning always have engaged many scholars in different fields of study such as linguistics, philosophy of language, psychology, logic and principles. In Islamic mysticism, the issues such as the language of mysticism, mystical words and meanings and the relation between the word and meaning, especially "figurative symbols", are fundamental too. This research is important for who are interested in theoretical mysticism and also for who are Salek and mysticism researchers. It also influences directly or indirectly on many fields. It should be mentioned that the intrinsic differences between mysticism and other logical and concrete sciences, makes many differences in form and usage of words and also its related debates such as reality and virtuality.  Negligence about these differences is the root of many misunderstandings and oppositions against Mysticism. Based upon the principles and lectures of mystics, especially Imam Khomeini and Ayatollah Javadi Amoli, this research tries to make a coherent this important mystical debate.